SOME OBSERVATIONS ON THE FISHERY AND BIOLOGY OF NEMATOPALAEMON TENUIPES (HENDERSON) AT BOMAY - Sukumaran, K K (Indian Journal of Fisheries, 2011)
Nematopalaemon tenuipes is caught by ’dol’ nets throughout the year at Sassoon Docks and from October to May at Versova, and also by trawlnets from March to Septemiber, from 15-40 m depth zone. The fishery shows wide annual fluctuations. The species spawns not less than 5-6 times in its whole life span. The females with berry in late stages migrating to slightly deeper waters, particularly dxiring March-November, result fluctuations in sex ratio. The number of eggs carried by a berried female of size 45-61 mm varied from 510 to 3250, depending on its size. The estimated total mortality coefiicients in males and females are found to be 4.70 and 3.73 at Versova while it is 4.16 and 3.36 at Sassoon Docks.